The Influence of Age Factor and Industrial Area on The Malignancy Rate of Bone Tumours - Devi, Namira Aisya; Kurniati, Yuni Prastyo (Journal La Medihealtico, 2024)
Bone tumour is a term for a group of tumours located in the bones. World Health Organization data in 2020 stated that the incidence rate of bone sarcoma in the Americas and Europe was 0.8 per 100,000 population. Industrial development, especially in areas with high population density, has environmental impacts such as air pollution and contamination of water sources. This has been associated with an increase in the prevalence of bone tumours in children. However, studies on this matter are still limited. This study aims to analyze the effect of industrial areas and age factors on the level of bone tumour malignancy. This study used observational analytics with a case-control design. Osteosarcoma as the case variable and GCT as the control variable. The sample used was 106, consisting of 53 osteosarcoma tumours and 53 GCT tumours. Age classification is divided into 0-18 years and 319 years. Industrial area classification is divided into <2.5 km and 32.5 km. Bivariate analysis using the chi square test. Has obtained approval from the Health Research Ethics Commission (KEPK) of RSUD dr. Moewardi with Number: 1.557/VI/HREC/2024. Results found no significant effect of age factor on the level of bone tumour malignancy (p-value=0.204). Meanwhile, an insignificant effect was also found between the proximity of residence to industrial areas on the level of bone tumour malignancy (p-value=0.121). This study shows that age factor and proximity of residence to industrial areas do not affect the level of bone tumour malignancy.